ASSESSING THE DIAGNOSTIC ACCURACY OF ULTRASONOGRAPHY AND MAMMOGRAPHY IN DETECTING BREAST MASSES: A CLINICAL CORRELATION WITH HISTOPATHOLOGICAL FINDINGS (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: To evaluate the efficacy of ultrasonography and mammography as a primary diagnostic tool for breast masses.Methodology: This retrospective  study involved 90 women aged 20 to 80 years with palpable breast lumps admitted in Services Hospital Lahore from 1st January 2020 to 30thJanuary 2022. Medical records of patients who underwent ultrasound or mammography and histopathological evaluation were systematically reviewed. Ethical approval was obtained from the Institutional Review Board vide letter No. IRB/2024/1496/SIMS dated 17-12-2024. The data was collected with information extracted on socio-demographic, clinical, and imaging findings, keeping identity of patient anonymous. Data were analyzed applying descriptive statistics, the Chi-square test for correlations, and the Kappa statistic to assess agreement between ultrasound and histological findings.Results: Majority patients were between 20-30 years (21.1%). Most participants were married (41.1%) or single (38.9%), and 76.7% were housewives. In terms of breast lump characteristics, 98.9% had unilateral lumps, and 94.4% had a single lesion. Oval-shaped lumps were most common (83.3%), and 80% had irregular outlines, often associated with malignancy. The BI-RADS classification showed 52.2% as BI-RADS 4 (suspicion of malignancy), and 24.4% as BI-RADS 5 (high suspicion). Needle biopsy was performed in 93.3% of cases. The Kappa value of 0.479 indicated moderate agreement between ultrasound and histology, with a p-value of 0.000, showing significant correlation. While ultrasound is useful, histopathology remains the gold standard for diagnosis.Conclusion: The overall efficacy of breast ultrasound and mammography in distinguishing between breast lumps was satisfactory; however, the prevalence of discordant cases underscores the necessity of clinical, radiological and pathological correlation to minimize diagnostic errors